2019
DOI: 10.21742/ijsbt.2019.7.2.05
|View full text |Cite
|
Sign up to set email alerts
|

A Consumer Recommendation System based on Big Data

Abstract: The recommendation system is a system to make consumers' choice easier by informing the result of combining information necessary for individuals in the information that consumers want in the market. Ultimately, it is a program to increase the satisfaction of consumers. In this study, consumers who choose cosmetics combine the existing attributes and extract the characteristics, and then recommend similar cosmetics, thereby enhancing the availability of consumers. For this purpose, the cosmetics classification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The transformation of the center's business model. According to the user's visit interest preferences, visit habits, visit paths and improved recommendation models, customized personalized services for target users are an important manifestation of Internet intelligence [19][20][21][22]. Starting from these modules, this chapter constructs the basic prototype of user access patterns [23] [24].…”
Section: Demand Analysismentioning
confidence: 99%
“…The transformation of the center's business model. According to the user's visit interest preferences, visit habits, visit paths and improved recommendation models, customized personalized services for target users are an important manifestation of Internet intelligence [19][20][21][22]. Starting from these modules, this chapter constructs the basic prototype of user access patterns [23] [24].…”
Section: Demand Analysismentioning
confidence: 99%
“…It is essentially an inductive process. The purpose of data analysis in customer relationship management is to discover hidden information in the data [13][14][15]. With the changing business needs of enterprises, the continuous updating of customer data, and the optimization of technology development systems, it is necessary to constantly adjust the established data model and to repeatedly carry out data mining to adapt to the requirements of enterprises [16] [17].…”
Section: Application Process Of Customer Relationship Management Undementioning
confidence: 99%
“…Regarding the research of social networks, the current research is mainly carried out from the perspective of communication and sociology. After long-term exploration, researchers have found that social networks also have the convenience of applying big data [11] and authenticity [12][13][14]. Social network data is born big data.…”
Section: The Value Of Social Network Big Data To Personal Credit Repomentioning
confidence: 99%